2023
DOI: 10.1002/pen.26285
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of zeolite, bentonite, and basalt fiber as natural reinforcing materials on the material properties of PPS and CF‐reinforced PPS

Abstract: This study was performed to expand the usage area of phenylene sulfide (PSS) by reducing its cost without deteriorating the material properties. For this purpose, mechanical, thermo‐mechanical and abrasion tests were conducted to composite materials obtained by adding carbon fiber (CF), basalt fiber (BF), zeolite, and bentonite into PPS, and the effects of additive type and ratio were examined. For the test samples, fabricated by the melt blending, the fiber content was 10 wt.%, while zeolite, and bentonite ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This result elaborated that the surface modification of basalt fiber by Ni‐MOF enabled to enhance the interfacial bond between the fiber and matrix, showing that the tenon and mortise structure microstructure of BF and EP affected the mechanical properties of the composite. [ 15 ] On the other hand, due to the incompatibility between Ni‐MOF sheets and EP monomer, some voids existed in the EP/BF/MOF composite, as highlighted in Figure 5B. These structure defects in EP/BF/MOF composite leaved open the possibility of improvement in mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result elaborated that the surface modification of basalt fiber by Ni‐MOF enabled to enhance the interfacial bond between the fiber and matrix, showing that the tenon and mortise structure microstructure of BF and EP affected the mechanical properties of the composite. [ 15 ] On the other hand, due to the incompatibility between Ni‐MOF sheets and EP monomer, some voids existed in the EP/BF/MOF composite, as highlighted in Figure 5B. These structure defects in EP/BF/MOF composite leaved open the possibility of improvement in mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they can also improve the tribological properties of composite materials. [14,15] For example, Khun et al studied the effect of chopped carbon fiber (SCF) on the tribological properties of EP composites, and the results showed that the incorporation of SCF was an effective way to improve the tribological properties of epoxy composites. When the SCF content was 20 wt%, the average friction coefficient of EP composites was 0.19, 74.64% lower than that of pure EP.…”
Section: Introductionmentioning
confidence: 99%
“…14 The mechanical properties of composites are dependent on the particle's size, interface adhesion between particle and matrix, and load sharing by particulates. 15,16 The finer size of the particle enhanced fracture toughness and increased the adhesion strength between the particle and matrix, which led to the enhancement in strength. 17 A few works reported on PFC have been discussed below, including various reinforcements using rice husk (RH), groundnut shell, and coir pith as potential fillers in an epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this challenge, researchers optimized thermodynamics, utilized surface modifications of the filler, and added low‐molecular‐weight compatibilizers to improve the interface between the filler and polymer 14 . The mechanical properties of composites are dependent on the particle's size, interface adhesion between particle and matrix, and load sharing by particulates 15,16 . The finer size of the particle enhanced fracture toughness and increased the adhesion strength between the particle and matrix, which led to the enhancement in strength 17 …”
Section: Introductionmentioning
confidence: 99%